KESEIMBANGAN EKOSISTEM DI PANTAI PALU KUNING MUNCAR BANYUWANGI - Eka Verawati (CONSERVA, 2023)
The ecosystem of Palu Kuning Beach is one of the beaches in Muncar, Banyuwangi which has components that make up the ecosystem, in an ecosystem there must be interactions between living things. the interactions in question are very diverse. The method used in this research is descriptive observation method and equipped with literature knowledge. Deer have an important role in the ecosystem as herbivores because they eat vegetation. Deer can also help control the growth of certain plants that can become excessive without natural predators. This can help maintain the balance of plant populations in the ecosystem, deer play a role in maintaining soil fertility and influence the composition of plant species that grow in an area. Based on observations at Pala Kuning beach, it is known that living things living in the area interact. The interactions that occur show that there are patterns of relationships in the ecosystem. Living things such as humans, animals, plants which are biotic components interact with abiotic components or non-living components, these interactions show the interrelationships and needs of the two components.